2021
DOI: 10.1039/d1ce01149a
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity behaviour of two roof-shaped host compounds in the presence of xylene and ethylbenzene guest mixtures

Abstract: In the present investigation, we compare the host and selectivity behaviour of two compounds, namely α,α-diphenyl-9,10-dihydro-9,10-ethanoanthracene-11-methanol H1 and α,α-bis(p-chlorophenyl)-9,10-dihydro-9,10-ethanoanthracene-11-methanol H2, when recrystallized from both singular and mixed isomers comprising the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The roof-shaped compounds derived from anthracene and fumaric acid were designed by Edwin Weber in 1996 and were shown to be highly effective host compounds for the complexation of a large variety of guest species. 15 In subsequent investigations in our own laboratories, these types of host compounds were demonstrated to possess enhanced selectivities in aromatic positional isomeric mixtures such as the xylenes (and ethylbenzene), 16–18 dichlorobenzenes, 19 the MePys (and Py), 20 methylanisoles (and anisole), 21,22 and bromoanisoles (and anisole). 23 In many of these recrystallization experiments that employed guest mixtures, host selectivity coefficients ( K ) were significant (greater than 10), alluding to the feasibility of separating such mixtures on a practical platform, as reported by Nassimbeni and co-workers.…”
Section: Introductionmentioning
confidence: 97%
“…The roof-shaped compounds derived from anthracene and fumaric acid were designed by Edwin Weber in 1996 and were shown to be highly effective host compounds for the complexation of a large variety of guest species. 15 In subsequent investigations in our own laboratories, these types of host compounds were demonstrated to possess enhanced selectivities in aromatic positional isomeric mixtures such as the xylenes (and ethylbenzene), 16–18 dichlorobenzenes, 19 the MePys (and Py), 20 methylanisoles (and anisole), 21,22 and bromoanisoles (and anisole). 23 In many of these recrystallization experiments that employed guest mixtures, host selectivity coefficients ( K ) were significant (greater than 10), alluding to the feasibility of separating such mixtures on a practical platform, as reported by Nassimbeni and co-workers.…”
Section: Introductionmentioning
confidence: 97%
“…It was reported that, more specifically, N , N ′-bis­(5-phenyl-5-dibenzo­[ a , d ]­cycloheptenyl)­ethylenediamine and its 10,11-dihydro analogue, N , N ′-bis­(5-phenyl-10,11-dihydro-5-dibenzo­[ a , d ]­cycloheptenyl)­ethylenediamine, possessed an overwhelming preference for p Xy and o Xy, respectively, when presented with such mixtures. Furthermore, other tricyclic fused systems based on the xanthenyl and thioxanthenyl systems have demonstrated selectivity behavior in such mixtures, favoring either p Xy or o Xy, dependent upon the molecular structure of the host compound employed. Additionally, it has been reported recently that the host compound derived from tartaric acid, ( R , R )-(−)-2,3-dimethoxy-1,1,4,4-tetraphenylbutane-1,4-diol, possessed an affinity for, also, the para isomer, while four roof shaped host compounds synthesized from anthracene by means of a Diels–Alder reaction also behaved selectively in EB/Xy mixtures. Interestingly, among all of these host compounds, only trans -α,α,α′,α′-tetra­(4-chlorophenyl)-9,10-dihydro-9,10-ethanoanthracene-11,12-dimethanol preferentially selected the meta isomer, while EB was never a favored guest species.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, this field of chemistry has successfully served as a separatory tool for various guest mixtures. Indeed, in our own laboratories, we have investigated the potential of host compounds based on tartaric acid, xanthone, and thioxanthone, and Edwin Weber’s roof-shaped host molecules , for the separation of Xy/EB mixtures. In an overwhelming majority of these experiments, the host compound displayed remarkable selectivity for one particular guest in the mixture, more usually p -Xy, but o -Xy also featured as the favored guest component in certain conditions.…”
Section: Introductionmentioning
confidence: 99%